Contextual Technology-Based Physics Module on Sound Absorption: Improving Critical Thinking Skills and Scientific Attitudes of Indonesian High School Students - Negoro, Ridho Adi; Rusilowati, Ani; Subali, Bambang (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2025)
The development of technology and science demands that education continues to innovate in enhancing students' critical thinking skills and scientific attitudes. One way to achieve this, specifically in physics education, is by developing practical modules that utilize experimental activities to foster critical thinking skills and scientific attitudes. This study aims to (1) develop a practical module on the sound absorption coefficient, (2) test the module's validity, (3) evaluate the practicality of the module in learning, and (4) assess the effectiveness of the module in improving students' critical thinking skills and scientific attitudes. This research employs an R&D approach, utilizing the 4D procedure: define, design, develop, and disseminate. Product trials were conducted using a pretest-posttest control group design. The results show that the developed practical module on the sound absorption coefficient has specific characteristics that integrate the measurement of physical parameters for technologies related to sound-absorbing materials, as well as excellent material and media validity, making it suitable for use and possessing a high level of practicality based on feedback from teachers and students. The module's readability test showed high ease for students in reading the content presented. Additionally, the module's effectiveness is demonstrated by significant improvements in critical thinking skills, with an N-gain of 0.85, and the achievement of scientific attitudes in students after using the practical module, with 79.54% of aspects achieved, which is higher compared to the group using conventional learning modules.